2018
DOI: 10.1021/acs.energyfuels.8b00761
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Predominantly Linear and Branched Waxes on Yield Stress and Elastic Modulus of Waxy Oils

Abstract: To assess the relationship of wax chemical structure and viscoelastic properties of waxy gels, model oils composed of single and blended waxes were prepared at a fixed concentration of 7.5 wt % and then gelled. The investigation encompassed four different well-characterized commercial paraffin waxes, solubilized in a mineral oil matrix. Previous rheological measurements pointed out that these systems reproduce essential features of crude oil gels (e.g., gel-like mechanical response) when gelled. Among the empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Previous rheological measurements confirmed that these model systems reproduce essential features of crude oil gels, exhibiting a low-temperature gel-like mechanical response to an imposed low-frequency oscillatory stress [30]. The physicochemical and structural properties of the wax and solvent used can be found in our previous work (L 29 wax) [30]. Seven different geometry configurations are employed, including combinations of smooth and grooved surfaces at oscillatory, creep, and steady-state rheological experiments.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…Previous rheological measurements confirmed that these model systems reproduce essential features of crude oil gels, exhibiting a low-temperature gel-like mechanical response to an imposed low-frequency oscillatory stress [30]. The physicochemical and structural properties of the wax and solvent used can be found in our previous work (L 29 wax) [30]. Seven different geometry configurations are employed, including combinations of smooth and grooved surfaces at oscillatory, creep, and steady-state rheological experiments.…”
Section: Introductionmentioning
confidence: 72%
“…A standard preparation protocol is followed to ensure reproducible rheological data [10,12]. Previous rheological measurements confirmed that these model systems reproduce essential features of crude oil gels, exhibiting a low-temperature gel-like mechanical response to an imposed low-frequency oscillatory stress [30]. The physicochemical and structural properties of the wax and solvent used can be found in our previous work (L 29 wax) [30].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations